Subjectivity Of Mariam: An Analysis Of Khaled Hosseini's Novel A Thousand Splendid Suns (2007) - Muaddatunikmah, Nur, Dr. Phil. Dewi Candraningrum, M.Ed, Dr. M. Thoyibi, M.S (2016)
Study on subjectivity has focused on power relations. The relation between Mariam and her father, Mariam and her mother, also Mariam and her husband, that is cannot be separated from her status as illegitimate child. Here, the writer tries to analyze subjectivity of Mariam based on Julia Kristeva's view. Finally, the writer draws a conclusion that by creating Mariam, Hosseini wants to deliver message that harami child, uneducated women, unsocial women, also wearing burqa women are the same, who need to be accepted, need to be loved back, and treated well. How pity, bad, and embarrassing life in the past, cannot become a reason to mock them or treat them bad. And all of human, whether man or woman have their right to get education as high as they want.